INCONGRUENCE AND HYPOCRITICAL BEHAVIOR FROM THE PERSPECTIVE OF NIFAQ: AN INTEGRATIVE PSYCHOLOGICAL-ISLAMIC LITERATURE REVIEW IN ISLAMIC GUIDANCE AND COUNSELING - Anikoh, Indifatul; Khotimah, Khusnul (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2026)
This article presents an integrative literature review that maps and synthesizes the conceptual relationships among incongruence in humanistic psychology, hypocritical behavior in social psychology, and the Islamic concept of nifaq, as a conceptual basis for the development of Islamic Guidance and Counseling (BKI). The analysis draws on a systematic review of relevant psychological and Islamic literature. The synthesis reveals that all three concepts share the same phenomenological anchor-the misalignment between internal values and external behavioral expression-yet each offers a distinct explanatory framework: humanistic psychology foregrounds the intrapersonal dimension, social psychology highlights contextual dynamics, while Islam emphasizes the spiritual-moral dimension. Their integration yields a more holistic and contextually sensitive model of understanding, with practical implications for developing BKI interventions that address both psychological and spiritual dimensions. The article also identifies limitations of Rogers' theory in collective cultural contexts such as Islamic boarding schools, and proposes the incorporation of interdependent self-construal as a conceptual bridge between Western psychology and the socio-cultural realities of Indonesian Muslim communities.